A study on security grade assignment model for mobile users in urban computing - Ko, Hoon (2014)
The relation between the information/knowledge expression and the physical expression can be involved as one of items for an ambient intelligent computing [2],[3]. Moreover, because there are so many contexts around user/spaces during a user movement, all appplcation which are using AmI for users are based on the relation between user devices and environments. In these situations, it is possible that the AmI may output the wrong result from unreliable contexts by attackers. Recently, establishing a server have been utilizes, so finding secure contexts and make contexts of higher security level for save communication have been given importance. Attackers try to put their devices on the expected path of all users in order to obtain users informationillegally or they may try to broadcast their SPAMS to users. This paper is an extensionof [11] which studies the Security Grade Assignment Model (SGAM) to set Cyber-Society Organization (CSO).